Juvenile recurrent respiratory papillomatosis: 10‐year audit and Australian prevalence estimates. (14th April 2016) - Novakovic, Daniel; Cheng, Alan T. L.; Baguley, Katherine; Walker, Paul; Harrison, Henley; Soma, Marlene; Malloy, Michael; Brotherton, Julia M. L.
Abstract : Objectives/Hypothesis: To estimate the prevalence of juvenile onset recurrent respiratory papillomatosis (RRP) in Australia, describe its epidemiological profile, and assess the positive predictive value of International Classification of Disease, 10th revision (ICD‐10) code D14.1 (benign neoplasm of larynx) in children for hospitalization due to RRP. Study Design: Retrospective case series. Methods: Retrospective case review undertaken at the three tertiary pediatric hospitals in New South Wales (Australia's largest state), by reviewing medical records of patients aged 0 to 16 years admitted during 2000–2009 containing the ICD‐10 Australian modification code D14.1 or other possible disease (D14.2–4, D14.3, D14.4) and RRP‐related procedure codes. For RRP diagnoses, we recorded treatment dates, length of stay, extent of disease, and surgical and adjuvant treatments. The positive predictive value (PPV) of code D14.1 and median number of hospitalizations per year were applied to national hospital separations data from 2000/2001 to 2012/2013 to estimate disease prevalence. Results: We identified 30 cases of RRP using code D14.1, which had a PPV of 98.1%, with no further cases identified using other codes. Fifty‐seven percent of cases were female, median age of onset was 36 months, and median treatment duration was 36 months (mean = 40 months, range = 1–118). There was one patient death. Between 2000 and 2013, the estimated national prevalence rate was 0.81 per 100, 000 aged < 15 years, peaking at age 5 to 9 years (1.1 per 100, 000). Conclusions: RRP prevalence can be monitored after human papillomavirus vaccination programs using routine hospital data. Level of Evidence: 4 Laryngoscope, 126:2827–2832, 2016